Pleural hydatidosis secondary to intrapulmonary echinococcosis: a case report - Čampar, Branko; Babić, Blagoje; Vukmirović, Mihailo (Vojnosanitetski pregled, 2026)
Introduction. Hydatid cysts are most often found in the liver and lungs, while other locations are rarely involved. Pleural hydatidosis, whether primary or secondary, is rarely seen in clinical practice. Case report. In this article, we present a case of a 33-year-old woman who presented with cough and dyspnea. Initial chest X-ray showed a large right-sided pleural effusion. Pleural hydatidosis was suspected based on the findings of the computed tomography scan of the chest. Right thoracotomy and cystectomy were performed. Albendazole was administered postoperatively for 6 months, and during this period, liver function tests and abdominal ultrasonography showed no abnormalities. Conclusion. This case emphasizes that pleural hydatidosis should be suspected in patients with pleural effusions and large cystic formations found on imaging, especially in endemic areas.